Exploration of Critical Success Factors of Logistics 4.0: A DEMATEL Approach - Shahbaz Khan; Rubee Singh; Abid Haleem; Jacinta Dsilva; Sadia Samar Ali (Logistics)
Background: Fourth Industrial Revolution (Industry 4.0) has revolutionized the operations, technologies, logistics and supply chain. To align with industry 4.0, the conventional logistics processes need to upgrade into digital logistics (logistics 4.0). This study aims to analyse the critical success factors of logistics 4.0. Methods: To accomplish this objective a comprehensive literature review is conducted for the identification of the critical success factors of logistics 4.0 with the expert’s input. These critical success factors are interrelated, and this interrelationship is explored through the DEMATEL approach. The applied methodology is categorised the critical success factors into cause-and-effect groups. Six factors belong to the cause group and the remaining four belong to the effect group. Results: The ‘top management commitment and support’, ‘aligning the initiatives of logistic 4.0 with organizational strategy’ and ‘technological infrastructure’ are the most influential critical success factors. This analysis also recognized the most influential and influenced factor amongst all identified critical success factors that will help the practitioners to optimal utilization of the resources. Conclusions: The findings of the study support the managers and practitioners in strategizing their effort for logistics 4.0 adoption.